Methyltrimethoxysilane (MTM) as a reagent for direct amidation of carboxylic acids - Braddock,D; Davies,J; Lickiss,P (Organic Letters, 2022)
Methyltrimethoxysilane [MTM, CH3Si(OMe)3] has been demonstrated to be an effective, inexpensive, and safe reagent for the direct amidation of carboxylic acids with amines. Two simple workup procedures that provide the pure amide product without the need for further purification have been developed. The first employs an aqueous base-mediated annihilation of MTM. The second involves simple product crystallization from the reaction mixture providing a low process mass intensity direct amidation protocol.